Creativity and Beaded Aesthetics: Thematic Analysis of the Beadworks of David Herbert Dale - Tolulope Ijisakin, Eyitayo; Ajiboye, Olusegun Jide; Abejide, Foluso Modupe; Adeyanju, Idowu Folorunso (Mediterranean Journal of Social Sciences, 2021)
In traditional Africa, beads function as adornments, as designation of royalty, and in many activities that have to do with commerce, religion, and healing among others. The use of beads has however found it ways into modern artistic expression. Literature abounds on the traditional use of beads, whereas there is a dearth of literature on creative usage of beads in contemporary Nigerian art. This study therefore examines creativity in the beadworks of David Herbert Dale. Data were collected through oral interviews with David Herbert Dale and relevant key informants such as art connoiseurs and gallery owners. This study relies on the theory of aesthetic response and functional theories of art; it also adopts the visual analysis approach to evince the aesthetics and deconstruct the contents of the beadworks. The paper argues that the beadworks of Dale are visual chronicles of historical, religious, economic, and socio-cultural aspects of Nigeria in particular, and Africa as a whole. Received: 7 September 2021 / Accepted: 24 October 2021 / Published: 5 November 2021